2012
DOI: 10.5055/ajdm.2012.0104
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different types of hazardous material respirators available to anesthesiologists

Abstract: The use of an NPR or PAPR does not preclude an anesthesiologist from successfully intubating, but practice is necessary. The slightly better performance with the NPR is weighed against the improved comfort of the PAPR and the fact that PAPR users could wear eyeglasses. Neither type of gear allowed the users to auscultate the lung fields to confirm correct endotracheal tube placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Multiple observational studies have indicated greater self-reported wearer comfort among users of PAPR technology 23 , 57 , 58 . A single cohort observational study found that all participants using N95 reported discomfort compared to 30 percent of wearers utilizing PAPR devices.…”
Section: Papr Use During Simulation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple observational studies have indicated greater self-reported wearer comfort among users of PAPR technology 23 , 57 , 58 . A single cohort observational study found that all participants using N95 reported discomfort compared to 30 percent of wearers utilizing PAPR devices.…”
Section: Papr Use During Simulation Studiesmentioning
confidence: 99%
“…It can be considered scientifically plausible that with their higher HEPA filter and greater assigned protection factor (APF), PAPR may be more protective during high risk aerosol generating procedures. Multiple observational studies have indicated greater self-reported wearer comfort among users of PAPR technology (23,57,58). A single cohort observational study found that all participants using N95 reported discomfort compared to 30 percent of wearers utilizing PAPR devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of powered air purifying respirators may prove to be more comfortable and allow the staff to wear eyeglasses while performing critical procedures such as intubation. 41 The correct gear, worn and sealed properly, should provide full protection from NAs. 26 Once a patient is fully decontaminated, there is limited risk of exposure for hospital personnel.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…Powered air-purifying respirator (PAPR) is the highest level of PPE recommended in COVID-19 era; however, N95 masks (or equivalent) are the most widely used PPE with this pandemic [ 1 ]. PAPR has several advantages over N95 masks, including comfort with longer use, better aerosol particulate protection, absence of fit test, facility of usage with facial hair, and reusability [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%